Multimedia Education for Inclusive Development: Exploring NCERT’s Open-Access Initiatives in India’s School Education System - Jain, Pooja; Babbar, Parveen (Indian Journal of Educational Technology, 2024)
The foundation for realising the national objective of a developed country rests on the provision of School Education. India’s school education system is the world’s largest, with a growing youthful population contributing to its potential for development. As a result, guaranteeing education accessible to everyone and providing multiple modes of access to educational resources for students and teachers have significant challenges and concerns. Several national-level organisations have taken numerous initiatives to enhance the quality of school education. This paper aims to elucidate the availability of multimedia content for disseminating and reaching all levels of school education. This study focuses on open-access materials developed and coordinated by NCERT. This research aims to bring to light the existence of e-content accessible to all stakeholders, such as students, teachers, parents, and educators in school education, which a trustworthy national institution in India has created.